The Effect of Realistic Mathematics Approach on Mathematical Problem Solving Ability of Elementary School Students - Hasrinah Hafid; Agustan Syamsuddin; Sulfasyah Sulfasyah (Pedagogik Journal of Islamic Elementary School, 2022)
This study aims to determine the effect of a realistic mathematical approach on the mathematical problem-solving ability of elementary school students. This study uses quantitative research with a non-equivalent control group design. The population in this study were all fifth-grade elementary school students from various schools in Tanete Rilau District, Barru Regency and the sample was drawn using simple random sampling. Instruments Data collection was carried out through a mathematical problem-solving ability test instrument. The data analysis technique used is descriptive and inferential analysis. The results based on descriptive analysis showed that the results of the problem-solving ability test of students who were given treatment with a realistic mathematical approach in the experimental class had a more significant effect than the control class with the average posttest results in the experimental class = 61.85 while in the control class = 46.40. The study's results based on inferential analysis using the independent sample t-test hypothesis test and the Manova test showed that learning with a realistic mathematics approach significantly affected the results obtained by the sig value. 0.000<0.05.